Interaction Between Low-Dose Aspirin and Nonsteroidal Anti-Inflammatory Drugs Can Compromise Aspirin’s Efficacy in Preventing Venous Thrombosis Following Total Joint Arthroplasty - Krauss, Eugene (Clin Appl Thromb Hemost, 2020)
Total joint arthroplasty is a rapid recovery procedure with patients optimized quickly in preparation for discharge. Two significant postoperative goals are effective pain management and prevention of postoperative venous thromboembolism (VTE). Low-risk patients receive aspirin 81 mg twice daily for VTE prophylaxis; this dosing regimen has been reduced over the past few years from 325 mg to 162 mg to 81 mg twice daily. Unless contraindications exist, all patients receive multimodal pain management that includes the use of celecoxib or meloxicam. Upon reduction of the aspirin dose to 81 mg twice daily, we rapidly identified 2 patients who developed a pulmonary embolus when celecoxib or meloxicam was administered concurrently with aspirin. The interaction between nonsteroidal anti-inflammatory drugs (NSAIDs) and low-dose aspirin varies among the different NSAIDs. It is also highly dependent on numerous factors, including time of administration, dose of aspirin, and both pharmacodynamics and dose of the NSAID. Real-world outcomes of concomitant administration of NSAIDs with low-dose aspirin led to increased incidence of VTE, possibly due to competitive inhibition of aspirin at platelet receptor sites. This interaction was mitigated by altering the administration times of both agents.